Chapter Le vestigia dei gesuati - Gagliardi, Isabella (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
The essay traces the salient historical steps of the Jesuat congregation, highlighting its genesis and development up to the year of its suppression (1668). The focus is on the dynamics triggered by the born of the Jesuat congregation, who grew on the border between the "church of the religious" and the "church of the laity", and on the use of intellectual energies of the Jesuat friars, because they were directed towards defining and safeguarding their own religious identity. The latter had two focal points: the example of Giovanni Colombini, its first "father", and, at the same time, the defence of the autonomy necessary to move interstitially between institutions, groups and movements. The historical parable of the Jesuats, in fact, clearly shows the importance assumed by the network of social relations for the constitution of the movement and for its progressive normalisation.